2020
DOI: 10.1101/2020.06.03.128561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin Mechanics Dictates Subdiffusion and Coarsening Dynamics of Embedded Condensates

Abstract: DNA is organized into chromatin, a complex polymeric material which stores information and controls gene expression. An emerging mechanism for biological organization, particularly within the crowded nucleus, is biomolecular phase separation into condensed droplets of protein and nucleic acids. However, the way in which chromatin impacts the dynamics of phase separation and condensate formation is poorly understood. Here, we utilize a powerful optogenetic strategy to examine the interplay of droplet coarsening… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…4f) and exactly coincide with 〈 〉. These distributions are relevant for the general case of soft-matter systems, but reflect an oversimplified scenario for living-cells, where we expect to find a limit to condensate size 45,47 .…”
Section: Theoretical Model Based On Particle Interactionssupporting
confidence: 62%
See 1 more Smart Citation
“…4f) and exactly coincide with 〈 〉. These distributions are relevant for the general case of soft-matter systems, but reflect an oversimplified scenario for living-cells, where we expect to find a limit to condensate size 45,47 .…”
Section: Theoretical Model Based On Particle Interactionssupporting
confidence: 62%
“…Condensates in living cells can only grow up to a given size 45,47 , therefore we impose an upper limit to condensate size in our model: condensates rapidly dissolve after reaching QER particles, i.e. , exponentially decreases for condensates with size above QER .…”
Section: Validation Of the Theoretical Model To Experimental Single Mmentioning
confidence: 99%
“…We suggest that the wild-type Hes repressor exhibits different properties upon binding to DNA. Recent work supporting this possibility comes from observations that condensate growth within a nucleus is limited by the surrounding chromatin 38 , if a condensate is bound to DNA this effect could be amplified. Additionally, classical genetic studies have identified several examples of insulators delimiting the spreading of silencers into neighboring, active loci 13,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Both mechanisms predict that the average droplet size, <R>, will increase with time, t, according to <R> ~ t 1/3 . The growth dynamics of in vitro nucleolar protein condensates, as well as nucleoli observed in developing Caenorhabditis elegans embryos, exhibits such t 1/3 coarsening dynamics; interestingly, emerging evidence suggests that the surrounding viscoelastic chromatin can decrease the scaling exponent for coarsening nuclear condensates 46 . Evidence of a saturation concentration, below which nucleolar phases do not assemble (Box 2) and that was shown to be important for several nucleolar proteins, provides additional quantitative support for the LLPS model in nucleolar organization 20,44 .…”
Section: Evidence From In Vitro Reconstitution Approachesmentioning
confidence: 98%